Using the product rule, differentiate: y = (x^2 - 1)(x^3 + 3).

y=(x2-1)(x3+3) let u=x2-1 u'=2x let v=x3+3 v'=3x2 uv'+u'v=(x2-1)(3x2)+(2x)(x3+3) =(3x4-3x2)+(2x4+6X) =5x4-3x2+6x

Related Maths A Level answers

All answers ▸

Differentiate: (12x^3)+ 4x + 7


A curve has an equation: (2x^2)*y +2x + 4y – cos(pi*y) = 17. Find dy/dx


Find the area R under the curve when f(x)=xcos(x) between the limits x=0 and x=2


Find the indefinite integral of sin(2x)(cos^2(x)) with respect to x.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences